1999
DOI: 10.1159/000017099
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging in Alzheimer’s Disease

Abstract: Diffusion-weighted imaging (DWI) is a powerful new magnetic resonance imaging technique for evaluating tissue pathophysiology in vivo. We performed DWI in three orthogonal spatial directions in 10 patients with mild to moderate Alzheimer’s disease (AD) and 11 control subjects. Average apparent diffusion coefficients (ADCavg) were calculated for gray matter regions, and anisotropy indexes were calculated for white matter regions. Global measures of atrophy and white matter hyperintensities (WMH) were obtained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 30 publications
5
48
1
1
Order By: Relevance
“…A general interpretation of these results is that diffusion changes in AD and MCI tend to occur in more posterior regions as opposed to anterior regions, as seen in normal aging [41,42]. Such increased posterior isotropic diffusion was found in a sample of AD patients [70], and differentiated AD from a sample of patients with vascular dementia [39].…”
Section: Studies Using Diffusion Weighted Imagingmentioning
confidence: 74%
See 1 more Smart Citation
“…A general interpretation of these results is that diffusion changes in AD and MCI tend to occur in more posterior regions as opposed to anterior regions, as seen in normal aging [41,42]. Such increased posterior isotropic diffusion was found in a sample of AD patients [70], and differentiated AD from a sample of patients with vascular dementia [39].…”
Section: Studies Using Diffusion Weighted Imagingmentioning
confidence: 74%
“…Increases in MD have been reported in patients with AD in the temporal lobes [40,51], hippocampus proper [51,70], splenium of the corpus callosum [38,70], posterior cingu- lum, occipital lobes and parietal lobes [51]. Increases in isotropic diffusion in AD have been reported in the corpus callosum (particularly the splenium) [38] and temporal lobe [40].…”
Section: Studies Using Diffusion Weighted Imagingmentioning
confidence: 99%
“…DWI studies on AD "all stages" patients [30,33] report no significant group differences in measurements of the anisotropy index (AI) -calculated by dividing the ADC perpendicular to the prominent callosal fiber direction by the ADC parallel to the predominant fiber direction of the CC -within the genu and splenium of the CC. On the other hand, Hanyu et al [28,29] using the same type of AI (that the authors called ADC ratio) found a decrease in the anterior (rostrum and genu) and posterior (isthmus and splenium) CC of AD "all stages" patients.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 99%
“…In fact, the main result mentioned above, that is atrophy mainly in the callosal anterior and posterior subregions, comes from studies of AD groups that included patients in different illness stages, ranging from mild to severe dementia [7,8,[10][11][12][14][15][16][17][18][19][23][24][25][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and sometimes selected using different diagnostic criteria [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…In human studies of patients with probable Alzheimer's disease, significant changes in diffusion in white matter have been observed (Rose et al, 2000;Sandson et al, 1999). In a study of early Alzheimer's disease, Choi et al found reduced FA, increased mean diffusivity, and increased radial diffusivity in superior frontal white matter (Choi et al, 2005).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%